Profitability enhancement by digital transformation and canvas digital model on strategic processes in post-Covid-19 in logistics SMEs - Rojas García, J.A. (2024)
The main objective of every Small and Medium Enterprise is to develop the ability to generate profits permanently over time; However, the Covid-19 pandemic significantly affected the global economy, generating an average reduction of 27% in global production and consumption, as well as a reduction in the use of labor, either due to reduced wages or reduction in working hours, which has had an impact on the increase in poverty. It is in this context that SMEs, with the aim of continuing to operate, implemented a strategy to reinvent themselves, which has been based on the greater use of the Internet and digital platforms with the aim of energizing their market or changing their line of business. , will thus develop activities in other areas or new services that did not exist before the moment of this reinvention. In this context, electronic commerce increased in a first stage, promoting the need to develop the so-called ‘last mile’ processes, which is provided most of the time by light logistics companies; However, the lack of agile and rapid implementation methodologies that facilitate the identification and selection of digital technologies appropriate to the processes of SMEs has caused the growth rate of e-commerce sales to decrease, which affects consumption and poverty reduction. Therefore, the objectives of this research are to provide a methodology that allows improving the strategic planning of the organization, adapting the strategy to changes in the environment in an agile and rapid manner, and identifying the resources and actions required that contribute to increasing the productivity through the Digital Canvas Model and Digital Transformation in logistics SMEs in the short term.